CREATIVITY OF PRESCHOOL CHILDREN REVIVAL THROUGH INTERACTIVE METHODS - Khamidova Gulbahor (American Journals, 2023)
The article highlights the issues of effective use by teachers of interactive methods in the organization of the pedagogical process in the formation of intellectual abilities in children in preschool educational institutions.
Keywords: Lesson, education, research, innovation, interactive, reflection, energizer.